2011
DOI: 10.1371/journal.ppat.1002071
|View full text |Cite
|
Sign up to set email alerts
|

Passively Administered Pooled Human Immunoglobulins Exert IL-10 Dependent Anti-Inflammatory Effects that Protect against Fatal HSV Encephalitis

Abstract: HSV-1 is the leading cause of sporadic encephalitis in humans. HSV infection of susceptible 129S6 mice results in fatal encephalitis (HSE) caused by massive inflammatory brainstem lesions comprising monocytes and neutrophils. During infection with pathogenic microorganisms or autoimmune disease, IgGs induce proinflammatory responses and recruit innate effector cells. In contrast, high dose intravenous immunoglobulins (IVIG) are an effective treatment for various autoimmune and inflammatory diseases because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(110 citation statements)
references
References 55 publications
11
98
1
Order By: Relevance
“…Importantly, IVIG lacking E-gp-specific antibodies still conferred significant protection, which showed that virus neutralization was not the main mechanism by which IVIG protected against WNV encephalitis. These findings extend our experience with IVIG protection against HSV1 encephalitis (Ramakrishna et al, 2011), and support the use of IVIG as an effective immunotherapeutic for treatment of suspected cases of WNV and HSV1 encephalitis.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Importantly, IVIG lacking E-gp-specific antibodies still conferred significant protection, which showed that virus neutralization was not the main mechanism by which IVIG protected against WNV encephalitis. These findings extend our experience with IVIG protection against HSV1 encephalitis (Ramakrishna et al, 2011), and support the use of IVIG as an effective immunotherapeutic for treatment of suspected cases of WNV and HSV1 encephalitis.…”
Section: Introductionsupporting
confidence: 82%
“…1c) despite being incapable of neutralizing virus infectivity (Table 1). This result showed that WNV neutralizing activity of IVIG was not critical for protection from WNV encephalitis and that alternative mechanisms could mediate protection (Vogt et al, 2011), which we anticipated based on our demonstration that IVIG protection against HSV1 encephalitis was independent of neutralizing antibodies (Ramakrishna et al, 2011).…”
Section: A Single Dose Of Ivig Is Able To Protect From Lethal Wnv Infmentioning
confidence: 62%
See 3 more Smart Citations